Menumbuhkan Budaya Hukum Baru Anti Kekerasan terhadap Perempuan - Sulistyowati Irianto (Antropologi Indonesia, 1999)
In this article, the author addresses the problem of violence towards women, with a focus on the violence in ethnic conflict and armed conflict. She takes the view that any legal system should be seen as having three components, i.e., legal substance, legal structure and legal culture, and that none of these components protect women from acts of violence. Citing articles from the criminal code, the authors show how the laws cannot protect women who are victims of violence and how some articles of the code in fact perpetuate injustice toward women. Following this, she shows how law enforcement officers who constitute the legal structure lack any gender awareness in their handling of cases. Finally, the attitudes and beliefs toward the law is the legal culture encourages the view that women are the property of men, especially in times of armed conflict.